Conversations That Connect: An Exploratory Study of Clubhouse Use and Motivations - Norhaili Massari; Mohd Muzhafar Idrus; Hazleena Baharun; Fariza Puteh Behak; Zarina Ashikin Zakaria; Normazla Ahmad Mahir; Akhdiat Abd. Malek; Kartini Mohd. Amin (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia